Perspectives on endoscopic submucosal dissection training in the United States: a survey analysis - Schlachterman, Alexander; Yang, Dennis; Goddard, April; Gotoda, Takuji; Draganov, Peter V. (Endoscopy International Open, 2018)
Background and study aims Endoscopic submucosal dissection (ESD) is a widely accepted method for en-bloc resection of dysplastic lesions and early cancer in Asia and Europe. A limiting factor in adoption of ESD in the United States is perceived lack of training opportunities. The aims of this study were to: (1) evaluate ESD experience of attendees at a University-sponsored ESD training course; (2) characterize effectiveness of the current ESD training regimen and its impact on ESD adoption in the United States; and (3) gauge trainees’ attitude towards ESD.Patients and methods An electronic anonymous survey was distributed to the 86 physicians who participated in the University of Florida’s annual ESD course from 2014 to 2016. Main outcomes included participants’ practice setting, prior training, current ESD techniques, and planned training. Results A total of 34 participants (40 %) completed the survey. Most of the respondents routinely use one or more endoscopic mucosal resection (EMR) techniques (97.1 %) in their practice. Most respondents (79 %) had no experience with ESD on humans prior to the ESD course. Following completion of course training, more participants reported ongoing hands-on ESD exposure, with 15/34 (44 %) having performed ESD in humans. Most participants identified potential hurdles for adoption of ESD.Conclusion A dedicated ESD training course with hands-on experience, under the guidance of experts, notably increased use of ESD among participants. Limited availability of structured training opportunities, concerns over procedural length, lack of adequate number of lesions, and potential for serious adverse events (AEs) were identified as the main factors slowing adoption of ESD in the United States.